Factors of forming safety competencies on water areas in student youth - Morozova, L.V.; Melnikova, T.I.; Vinogradova, O.P. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify the factors that reduce the risk of accidents based on students’ mastery of swimming competencies. Methods and structure of the study. The study was conducted using a cross-sectional design with a questionnaire that included questions related to socio-demographic data, organizational factors, and the level of swimming competencies. A survey was conducted of 125 students of a managerial university of all years of study: 57 (47.7%) female students and 68 (52.3%) male students. Results and conclusions. Students’ mastery of swimming skills before entering a higher educational institution ensures the effective formation of competencies related to safety on water bodies. By the end of their studies, senior students have a better command of competitive and applied swimming skills. The formation of skills in performing applied techniques and actions is a priority in the field of safety on water bodies.